Current state of research on the use of technology in language teacher education and professional development. Issue 4 (2nd August 2022) - Bahari, Akbar; Barrot, Jessie S.; Sarkhosh, Mehdi
Abstract : Educational technology (ET) can reportedly provide innovative resources to improve the language learning process. However, few studies have elaborated on the use of ET for language teacher education and professional development. To shed light on the reported challenges and affordances of digital technology in language teacher education and professional development, the authors conducted a systematic review of recent technology‐assisted language teacher education studies. The contributions of the study to the field of technology‐assisted language learning (TALL) are twofold. Pedagogically, the study conveys a list of affordances that can inform TALL practitioners about the tested and reported efficacies that can be used in teacher education and professional development programs. Theoretically, the findings inform TALL researchers about the challenges and limitations that need to be overcome to facilitate the use of ET in teacher education and professional development. The findings also help predict the future trend of TALL research on teacher education and professional development based on studies conducted from 2010 to 2021.